Hemolytic Uremic Syndrome: “Diagnosis and Management in Pediatric Population" - Hafeez, Farkhanda; Asim, Sadaf; Akhtar, Naureen; Ahmad, Junaid (Pakistan Journal of Kidney Diseases, 2021)
The review article” Hemolytic Uremic Syndrome: Diagnosis and Management in Pediatric Population” is an update on different types of hemolytic syndrome, its diagnosis and treatment. This write up also sheds light on limitation in its management in a resource limited country and suggestions to overcome it. It is hoped that it will generate interest and will encourage the readers to share their experiences.